Essentials of negotiation - Lewicki, Roy J. (Boston Mcgraw-Hill, 2016)
Essentials of Negotiation, 5e is a condensed version of the main text, Negotiation, Sixth Edition. It explores the major concepts and theories of the psychology of bargaining and negotiation, and the dynamics of interpersonal and inter-group conflict and its resolution. Twelve of the 20 chapters from the main text have been included in this edition, several chapters having been condensed for this volume. Those condensed chapters have shifted from a more research-oriented focus to a more fundamental focus on issues such as critical negotiation subprocesses, multiparty negotiations, and the influence of international and cross-cultural differences on the negotiation process.
Includes bibliographical references (p. 228-249) and index
Keywords: Negotiation in business